How training affects Australian paediatricians' management of obesity. Issue 1 (13th July 2012) - Wake, Melissa; Campbell, Michele W; Turner, Megan; Price, Anna; Sabin, Matthew A; Davis, Elizabeth; Baur, Louise A
Abstract : Objective: Secondary care could be the optimal sector for managing child and adolescent obesity, given low primary care uptake and limited tertiary services. We aimed to determine Australian paediatricians' self-reported competence and training in managing obesity and, in a linked patient-level audit, whether these predict rates of measurement and obesity diagnosis. Design, setting and patients: Australian Paediatric Research Network members completed an online survey, plus a prospective patient-level audit of up to 100 consecutive consultations over 2 weeks. Main outcome measures: Survey : self-reported competencies, training in and use of clinical skills in obesity and its comorbidities. Audit : paediatricians reported each child's height, weight, age, sex and diagnoses including overweight/obesity. Results: Of 166 (44.7% response) paediatricians, most felt very/quite competent in assessing (89%) and managing (68%) obesity, but few in making a difference to obesity (20%) or managing hypertension (45%), insulin resistance (32%), fatty liver disease (22%) or dyslipidaemia (21%). The audit of 200 (66.2% response) paediatricians included 8345 patients. On average paediatricians recorded height and weight for 66.5% of patients (SD 30.0%, range 0–100%). Of the 296 (12.3%) patients obese by CDC cutpoints, 118 (39.9%) were diagnosed as obese; perceived competence increased the odds of recording this diagnosis but not measurement. Training levels were low, showed little association with measurement or obesity diagnosis, and skills learnt were not routinely used. Conclusions: There is a clear need for better paediatrician training in obesity management. However, care and outcomes for obese children are unlikely to improve unless effective management models can be operationalised systematically.